Challenges in the christian vocation in sub-saharan Africa : from the colonial library to contemporary african literature - (:unkn) unknown (My University, 2022)
The call to convert to Christianity in Sub-Saharan Africa was accomplished by western missionaries during colonisation according to the triptych: “Christianisation”, “civilisation”, and “promotion of county”. The narrative of these missionary representations in Colonial literature created an asymmetric relationship between missionaries and those whom they evangelised, that is, one of domination. However, African literature questions missionary discourse by defending African culture. Political independence and the Second Vatican Council (Vatican II) sought to resolve this conflicted relationship by recognizing the capacities and values of indigenous people. Nevertheless, the effort to understand the Christian Faith presents several difficulties and crises, both individual and collective. Thus, throughout the works studied, multiple challenges, both implicit and explicit, underly the question of conversion to Christianity in Sub-Saharan Africa.
Keywords: African Research